2015
DOI: 10.1371/journal.pone.0132883
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Type II Diabetes Care in Primary Health Care Centers in Kuwait: Employment of a Diabetes Quality Indicator Set (DQIS)

Abstract: Diabetes Mellitus is one of the major public health challenges, affecting more than 347 million adults worldwide. The impact of diabetes necessitates assessing the quality of care received by people with diabetes, especially in countries with a significant diabetes burden such as Kuwait. This paper aimed at piloting an approach for measuring Type II diabetes care performance through the use of a diabetes quality indicator set (DQIS) in primary health care. The DQIS for Kuwait was adapted from that developed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
(22 reference statements)
4
12
2
Order By: Relevance
“…Data from Kuwait found that doubling of the HbA 1c measurements (from 30% to 63%) between 2010 and 2012, was associated with a decrease in the rate of poorly controlled HbA 1c from around 80% to 55% [29]. Our findings regarding glycemic control are comparable with those of studies in other Arab countries, 26.4% patients achieved HbA 1c < 6.5% and 41.8% ones achieved HbA 1c < 7.5%.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Data from Kuwait found that doubling of the HbA 1c measurements (from 30% to 63%) between 2010 and 2012, was associated with a decrease in the rate of poorly controlled HbA 1c from around 80% to 55% [29]. Our findings regarding glycemic control are comparable with those of studies in other Arab countries, 26.4% patients achieved HbA 1c < 6.5% and 41.8% ones achieved HbA 1c < 7.5%.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, 41.5% of patients had HbA 1c above 8.5%, this is less than the 54% reported in a study looking at diabetics in primary care settings in Saudia, and the 55.4% reported rate for poor control in Kuwait [29,34].…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Poor glycaemic control is defined as a glycated haemoglobin (HbA1c) equal to or above 7% or a fasting plasma sugar (FPS) above 7.2 mmol/l for adults who are not pregnant [ 7 ]. Poor glycaemic control (HbA1c > 7%) among people with type 2 diabetes mellitus (T2DM) in the GCC countries is common, ranging between 59% and 70.7% in Saudi Arabia [ 8 , 9 ], 68% and 69% in the UAE [ 10 , 11 ], 86.5% and 88.8% in Bahrain [ 12 , 13 ], and 54% and 65% in Oman [ 14 , 15 ], while a study reported that 55% of people with T2DM in Kuwait have HbA1c > 9% [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could be achieved by implementing strategies for assessing and improving the quality of the health care services provided. 24 , 26 , 51 Also, at the governmental level, reinforcing and strengthening strategies for prevention and early diagnosis of T2DM should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%